2015
DOI: 10.1002/polb.23933
|View full text |Cite
|
Sign up to set email alerts
|

An in situ GISAXS study of selective solvent vapor annealing in thin block copolymer films: Symmetry breaking of in‐plane sphere order upon deswelling

Abstract: Thin films of asymmetric poly(styrene-b-4-vinylpyridine) (PS-b-P4VP) block copolymers are studied by means of in situ grazing-incidence small-angle X-ray scattering (GISAXS) during solvent vapor annealing in tetrahydrofuran, a solvent selective for the PS majority block of the copolymer. Upon swelling, PS-b-P4VP block copolymers form hexagonal arrays of spherical P4VP microdomains in a PS matrix in films 7-9 layers thick. Deswelling the films induces a transition from hexagonal to face-centered orthorhombic (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 41 publications
2
61
0
Order By: Relevance
“…Solvent vapor annealing (SVA) is a widely used method to obtain highly ordered nanostructured BCP thin films, which also has been applied to modify the BCP thin film morphology . In recent years, the efficiency of this approach was improved by the so‐called warm or solvothermal vapor annealing (STVA) .…”
Section: Introductionmentioning
confidence: 99%
“…Solvent vapor annealing (SVA) is a widely used method to obtain highly ordered nanostructured BCP thin films, which also has been applied to modify the BCP thin film morphology . In recent years, the efficiency of this approach was improved by the so‐called warm or solvothermal vapor annealing (STVA) .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Gunkel et al [197] found an in-plane restructuring of the P4VP spheres in a PS matrix. Swelling in THF (which is selective for the PS matrix) leads to hexagonally packed microdomains.…”
Section: Figure 16mentioning
confidence: 95%
“…SVA in combination with in-situ GISAXS has been shown to be able to alter the morphology of BCP thin films [144,193,194,197]. Using the same PMS-b-PHOST DBCP as described in (Figure 15, Table 3).…”
Section: Studies Aiming At Altering the Morphologymentioning
confidence: 99%
“…GISAXS is a useful technique and it has been applied to many polymeric functional materials in the form of thin films . Especially for block copolymer thin films, it is a powerful method for analyzing nanostructure and its orientation . It should also be noted that time‐resolved GISAXS measurements have been conducted for analyzing nanostructure formation process during the spin‐cast process, during the slot‐die coating process and during the solvent vapor annealing process .…”
Section: Grazing‐incidence Saxsmentioning
confidence: 99%
“…Especially for block copolymer thin films, it is a powerful method for analyzing nanostructure and its orientation . It should also be noted that time‐resolved GISAXS measurements have been conducted for analyzing nanostructure formation process during the spin‐cast process, during the slot‐die coating process and during the solvent vapor annealing process . Future perspectives of this method enhanced using XFEL femtosecond pulses and full coherence have been presented in the review by Ree .…”
Section: Grazing‐incidence Saxsmentioning
confidence: 99%